THEORIES OF POVERTY - Junaidi, Akhmad; Rif’ah, Nurul; Indriyani, Iin (LPPM Universitas Bina Bangsa, 2024)
Poverty is a major problem that occurs in almost all countries, especially in developing countries. Poverty is a condition in which a person is unable to meet their needs. According to the World Bank (2015), a person will be considered poor if they have an income less than the income standard. Poverty as a low standard of living can be seen directly in the level of health and moral life. According to Tambunan (2019) there are factors that influence poverty, namely the level and rate of growth, labor productivity, net wage levels, income distribution, employment opportunities, inflation rates, taxes and subsidies, investment, natural resources, availability of public facilities such as basic education, health, transportation, electricity, water, and residential locations, cultural culture, politics, and natural disasters. The economic recovery of a country has a positive impact on improving people's welfare. People's welfare can be seen from the conditions of the community in the area. The poorer people in the area, the less prosperous the area is, and vice versa, the fewer poor people in the area, the area.